Management and characterization of stable fly larval habitats at round hay bale feeding sites in pastures - Talley, Justin L. (Kansas State University, 2008)
Stable flies, Stomoxys calcitrans (L.), are a serious pest to beef cattle in confined animal feeding operations (CAFOs) by causing economic losses in the form of reduced feed intake and feed efficiency, resulting in reduced weight gain. Integration of sanitation, parasitoids, and residual insecticides offers a much-needed reduction of this pest's impact on CAFOs. In the past two decades, stable flies have become the most important pest of pastured cattle. Further impact that stable flies have on cattle is when cattle seek protection from stable flies by standing in water, which results in water pollution with fecal matter, in addition to reduced foraging time. Sites of winter feeding of round hay bales have demonstrated to be important habitats for stable fly development during spring/summer. Cattle feeding on round bales can waste as much as 40% of the total amount of hay when fed in conventional ring feeders. Hay wastage is largely a function of the type of feeding method and the amount of agonistic behavior of the cattle. Feeding methods range from rolling hay directly onto the ground to the use of various types of feeders. Since traditional control methods utilized in CAFOs against stable flies have not been evaluated in pastures, producers rely heavily on organic insecticides in efforts to control this pest. At this time, there are no effective control methods available for stable fly management on pastured cattle. This research examined different management strategies that could minimize or eliminate stable fly larval habitats by reducing the amount of hay wasted being mixed with manure. In addition, different hay and manure mixtures were compared to characterize the larval habitat at these hay-feeding sites. Finally, the efficacy of boric acid, Metarhizium anisopliae, and tetrachlorvinphos in controlling the development of stable flies in hay substrates was evaluated.
Keywords: stable flies; round hay bales; Biology, Entomology (0353)